Revealing Investor Motivation in Making Investment Decisions in the Capital Market - Maiercherinra Daud; Ruri Mangera; Danar Irianto Irianto (Politeknik Negeri Batam, 2022)
This study aims to find out more deeply what investors consider in making investment decisions in the Indonesian Capital Market. The research method used in this study is a qualitative method through an interpretive paradigm using a phenomenological approach. The results of this study indicate that each informant has different considerations in making decisions to invest. Some like risk and some don't like risk. This can be seen from the results of interviews with informants, some use accounting information (fundamental analysis) and some use information based on stock price fluctuations by looking at the conditions of the business environment (technical analysis).